IMPLEMENTATION OF CAREER GUIDELINES FOR STRENGTHENING THE PKL (FIELD WORK PRACTICE) PROGRAM FOR CLASS XI ATU AT SMK NEGERI KALIBARU - Muhammad Rehan Solehudin; Harwanti Noviandari; Agus Mursidi (International Jurnal of Education Schoolars, 2021)
Muhammad Rehan Solehudin, 2021; Implementation of Career Guidance for Strengthening the Pkl Program (Field Work Practice) Class XI ATU at SMK Negeri Kalibaru.43 pages; Counseling Guidance Study Program, Faculty of Teacher Training and Education, PGRI Banyuwangi University. Supervisor: (I) Prof. Dr. Miftahul Arifin, M.Pd (II) Dr. Agus Mursidi, M.Pd. This study aims to identify and describe the role of BK teachers in strengthening the PKL program. Data were collected using direct interview techniques to students of SMK Negeri Kalibaru majoring in ATU and also alumni of SMK Negeri Kalibaru majoring in ATU who were already working and continuing their studies in higher education. Researchers in addition to collecting data through direct interviews, researchers also use observation and documentation in order to obtain more in-depth information. The method used in this study uses a qualitative approach. The role of BK teachers in implementing career guidance for strengthening the field work practice program for class XI ATU at SMK Negeri Kalibaru has been carried out well during teaching and learning activities and outside teaching and learning. The role of the BK teacher in implementing career guidance for class XI is as a facilitator who has a very big responsibility in helping students' talents and interests. BK teachers at SMK Negeri Kalibaru spend a lot of time with students in the hope that later students from SMK Negeri Kalibaru, especially those majoring in ATU, will be able to continue their studies at university or go straight to work